Defying Expectations of Heritage-Seeking: Forming Identity through Education Abroad (Comparative & International Education Series, 2022)
While waiting to deplane, I told myself to remember this moment because as soon as I put my feet on the ground, my life would be changed forever. I was on a journey to learn about China, the country where I was born, and I believed that when I got off the plane, I would be home. I imagined what it would be like to walk down the streets and see people who looked like me. I couldn’t wait to try foods that were local to the region where I was born and potentially even meet people who shared a common ancestry with me. From the stories I heard from other adoptees, it would feel like putting that last piece of my identity snugly into the puzzle where it belonged. As I look back on the photos from my journey almost a decade later, one of the first pictures in the album is a blurry image of the airport seen through the window of the transfer bus on the way to the hotel. The caption reads, “first glimpses of China.” I wanted to be sure to take pictures of everything I saw so that I could remember the trip that would help me understand who I am.